Advancements in Pediatric Dermatology: Balancing Ethics and Ensuring Patient Safety - Tahir Kamal (Journal of Pakistan Association of Dermatologists, 2025)
Significant improvements in diagnosis and treatment of childhood skin disease have been made in pediatric dermatology for children with complex skin disease. At the same time, however, these advancements beget ethics problems like consent in pediatric care, equitable access to treatment and the application of new therapies with long term safety profiles proven during staged testing. This article discusses the ethical challenges and safety issues in pediatric dermatology and outlines that the patient centered approach, research integrity and clinical guidelines should be considered during practice. The pediatric dermatology specializes in diagnosis and treatment of skin, hair, and nail disorders of children with unique physiological and psychological conditions. Since the prevalence of pediatric skin disorders such as atopic dermatitis, psoriasis and rare genodermatoses is growing, a need has arisen for a special treatment. These advances come along with ethical challenges and patients safety concerns, and thus, a more nuanced understanding of pediatric care’s moral and clinical aspects.